Identification of genetic marker for CSN3 gene in Karan Fries (Holstein Friesian crossbred) population - KOUR, ANEET; CHAKRAVARTY, A K; GUPTA, A K; RAINA, VARINDER (The Indian Journal of Animal Sciences, 2018)
The study was conducted to identify genetic marker for CSN3 gene related to higher casein yield in 78 pedigreed Karan Fries (HF crossbred) cattle population at ICAR-NDRI, Karnal. PCR-RFLP of exon 4 region of CSN3 gene, carried out using HindIII restriction endonuclease, revealed three genotypesâ€”CC, CA and AA with frequencies as 0.18, 0.67 and 0.15 and frequency of C and A allele as 0.51 and 0.49. Eight SNPs (C296A, C380T, C383T, G394T, C419A, G480A, A488T and G529T) were revealed through sequencing. Using Regression model, SNP (C419A) in the targeted region was found to contribute an increase of 1.8 g in κ-casein yield (CY) which was 2.81% of CY (63.62 g) in average test day milk yield (ATDMY). After screening progenies for SNPs based on Daughter-Dam Design, SNP G480A was found to be a potential genetic marker, contributing an increase of 7.5 g in CY (11.79% of CY in ATDMY).